Ultraviolet and infrared radiation in Australia: assessing the benefits, risks, and optimal exposure guidelines - Sharma, Kirti; Dixon, Katie M.; Münch, Gerald; Chang, Dennis; Zhou, Xian (Frontiers in Public Health, 2024)
Despite extensive research, determining the optimal level of sunlight exposure for human health remains a challenge, emphasizing the need for ongoing scientific inquiry into this critical aspect of human well-being. This review aims to elucidate how different components of the solar spectrum, particularly near-infrared (NIR) radiation and ultraviolet radiation (UVR) affect human health in diverse ways depending on factors such as time of day and duration of exposure. Sunlight has beneficial effects from the production of melatonin by NIR and vitamin D by UVB. Sunlight also causes harmful effects as evidenced by oxidative stress and DNA damage. Exposure to morning and evening sunlight when the UV index is below 3 is suggested to be beneficial for harnessing its positive effects while avoiding the harmful effects of UVR when the UV index is 3 or higher. Understanding the optimal timing and duration of sunlight exposure is crucial for harnessing its beneficial effects while minimizing its harmful consequences by adopting appropriate sun protection measures. By adhering to sun protection guidelines when the UV index is 3 or more and incorporating strategic exposure to NIR rays when the UV index is less than 3, individuals can optimize their health outcomes while mitigating the risks associated with sun exposure. Given that the effects of sun exposure can be both harmful and beneficial, and Australia’s unique geographical position where it experiences the highest levels of exposure to sunlight, it is vital to understand the appropriate level and timing of sun exposure to live healthy under the Australian sun.